When pictures speak: the perception of users undergoing residential drug addiction treament concerning their integration using photovoice - Casals, Laia; Calvo, Fran (Acciones e Investigaciones Sociales, 2022)
People receiving treatment for drug addiction have to face reintegration after completing their therapy. This is based on the acquisition of skills to achieve full autonomy. Reintegration is implemented when a situation involving exclusion has occurred, in this case associated with the use of drugs. The aim of this study was to ascertain the viewpoint of the individuals receiving residential treatment for drug addction regarding their own integration process. Data was gathered using a qualitative approach using the Photovoice technique over ten sessions, in which fourteen users participated from a therapeutic group, along with two halfway houses specialising in providing aid to drug addicts. The results indicated that the participants believed reintegration depended on themselves and the use they made of their stay at the halfway house. Nevertheless, they also evaluated external differences such as stigmatisation in the form of mistrust, the lack of information concerning addiction on the part of society, or the lack or resources and qualified professionals. In conclusion, the participants showed great motivation to tackle their integration satisfactorily considering the difficulties they were likely to encounter. Finally, the use of the Photovoice technique was perceived to be positive by the participants, especially as a means of participation and expression.